2015
DOI: 10.1016/j.amepre.2015.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Leisure-Time Physical Activity, Falls, and Fall Injuries in Middle-Aged Adults

Abstract: Similar to older adults, middle-aged adults who engage in LTPA report fewer falls and fall-related injuries. Upon further confirmation of the relationship between LTPA and falls among middle-aged adults, fall prevention interventions could be developed for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 40 publications
(50 reference statements)
3
37
0
1
Order By: Relevance
“…27 To our knowledge, the present study is the only US prospective study of accelerometer-measured physical activity with careful falls surveillance in a large population of older women, the group at highest risk of falls and fall-related injuries. 26 The results of this observational study support no association of higher levels of MVPA with fall risk in community-dwelling ambulatory women. Consistent with the present study, the ActiFE-Ulm Study, conducted in Southern Germany among 1214 older adults, found no increased risk of falls among older men or women with higher levels of accelerometer-measured PA. 30 …”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…27 To our knowledge, the present study is the only US prospective study of accelerometer-measured physical activity with careful falls surveillance in a large population of older women, the group at highest risk of falls and fall-related injuries. 26 The results of this observational study support no association of higher levels of MVPA with fall risk in community-dwelling ambulatory women. Consistent with the present study, the ActiFE-Ulm Study, conducted in Southern Germany among 1214 older adults, found no increased risk of falls among older men or women with higher levels of accelerometer-measured PA. 30 …”
Section: Discussionmentioning
confidence: 55%
“…26 Self-reported leisure time physical activity is poorly correlated with accelerometry measurements of MVPA 27 and may be especially inaccurate in older adults and women. 28,29 Accelerometers capture movements during daily life beyond those identified as leisure-time exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies identified the relationship between fall risk and level of physical activity among the elderly population in various countries. It was reported that physical activities ranging from leisure time physical activity to the daily moderate to vigorous-intensity physical activity in older adults will prevent and reduce the incidence of fall9, 10 ) . There are many studies regarding this concern, however, the studies exploring the correlation between physical activity level and fall risk among community dwelling Malaysian older adults is limited.…”
Section: Introductionmentioning
confidence: 99%
“…32 Nevertheless, studies where the method did not depend on long-term recall show a comparable age distribution of falls. 2,48 The implications of more recent versus less recent falls could not be explored since we did not collect that information. Finally, use of multiple comparisons is another potential limitation.…”
Section: Discussionmentioning
confidence: 99%